2010
DOI: 10.1186/1476-4598-9-196
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids reduce ErbB2-driven breast cancer progression through Akt inhibition

Abstract: BackgroundErbB2-positive breast cancer is characterized by highly aggressive phenotypes and reduced responsiveness to standard therapies. Although specific ErbB2-targeted therapies have been designed, only a small percentage of patients respond to these treatments and most of them eventually relapse. The existence of this population of particularly aggressive and non-responding or relapsing patients urges the search for novel therapies. The purpose of this study was to determine whether cannabinoids might cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
153
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 35 publications
6
153
0
4
Order By: Relevance
“…This was in agreement with the work of others that suggested the effects of cannabinoids on MAPK was both dose-dependent and cell line specific (15,23). In addition to MAPK, the PI3-kinase/AKT pathway was also considered as it has also been linked to cannabinoid action and is an important determinant of cell fate (28). Our results showed modest reductions in pAKT, which was most apparent at the higher concentrations of CBD.…”
Section: Discussionsupporting
confidence: 93%
“…This was in agreement with the work of others that suggested the effects of cannabinoids on MAPK was both dose-dependent and cell line specific (15,23). In addition to MAPK, the PI3-kinase/AKT pathway was also considered as it has also been linked to cannabinoid action and is an important determinant of cell fate (28). Our results showed modest reductions in pAKT, which was most apparent at the higher concentrations of CBD.…”
Section: Discussionsupporting
confidence: 93%
“…Phosphorylated Akt has been shown to correlate with poor survival and several clinical trials are concerned with inhibiting the PI3K/Akt /mTOR pathway (29)(30)(31)(32). In this work we have shown that reported that deletion of Akt2 in both mice and humans can provoke insulin resistance (33,34).…”
Section: Discussionmentioning
confidence: 60%
“…Cannabinoids (the active components of C. sativa) and their derivatives have received great attention in recent years due to their applications as anti-tumour drugs (15)(16)(17)(18). Due to the fact that cannabinoid receptors (CB1 and CB2) are overexpressed in primary human breast tumors compared to normal breast tissues, agonists of cannabinoid receptors are offered as a novel strategy to treat cancer (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis sativa may cause antitumor effects by various mechanisms, including inhibition of cell growth and tumor angiogenesis invasion, induction of cell death, and metastasis (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%